Managing Long COVID in East Asia and the Pacific - Arur, Aneesa; Islamaj, Ergys; Kim, Young Eun; Le, Duong Trung; Mattoo, Aaditya; Somanathan, Aparnaa (World Bank, Malaysia, 2021)
The highly contagious Delta variant is fueling new outbreaks in East Asia and the Pacific (EAP). It is becoming evident that COVID-19 (coronavirus) is not leaving any time soon and may be here to stay. Countries with high vaccination coverage show, however, that transition to a relativelybenign phase of "managed endemicity" may be possible. At current trends, and given vaccine availability, many EAP countries are expected to vaccinate more than 60 percent of their populations by the first half of next year. Achieving and sustaining high coverage will require improving distribution capacity, overcoming vaccine hesitancy, and expanding regional production of vaccines to ensure reliable supplies for persistent COVID-19. Countries will also need to sustain the process of testing, tracing, and isolation, as well as precautions such as social distancing and wearing masks. Finally, countries need to strengthen their health systems to cope with long COVID.